Transcriptome analysis of haploid male gametophyte development in Arabidopsis - Honys, David; Twell, David (Genome biology, 2004)
BACKGROUND: The haploid male gametophyte generation of flowering plants consists of two- or three-celled pollen grains. This functional specialization is thought to be a key factor in the evolutionary success of flowering plants. Moreover, pollen ontogeny is also an attractive model in which to dissect cellular networks that control cell growth, asymmetric cell division and cellular differentiation. Our objective, and an essential step towards the detailed understanding of these processes, was to comprehensively define the male haploid transcriptome throughout development. RESULTS: We have developed staged spore isolation procedures for Arabidopsis and used Affymetrix ATH1 genome arrays to identify a total of 13,977 male gametophyte-expressed mRNAs, 9.7% of which were male-gametophyte-specific. The transition from bicellular to tricellular pollen was accompanied by a decline in the number of diverse mRNA species and an increase in the proportion of male gametophyte-specific transcripts. Expression profiles of regulatory proteins and distinct clusters of coexpressed genes were identified that could correspond to components of gametophytic regulatory networks. Moreover, integration of transcriptome and experimental data revealed the early synthesis of translation factors and their requirement to support pollen tube growth. CONCLUSIONS: The progression from proliferating microspores to terminally differentiated pollen is characterized by large-scale repression of early program genes and the activation of a unique late gene-expression program in maturing pollen. These data provide a quantum increase in knowledge concerning gametophytic transcription and lay the foundations for new genomic-led studies of the regulatory networks and cellular functions that operate to specify male gametophyte development.
Keywords: Genes, Plant; Pollen; Gene Expression Profiling; Genome, Plant; vývojová regulace genové exprese; Homeodomain Proteins; rostlinné geny; genom rostlinný; Arabidopsis Proteins; pyl; haploidie; Transcription Factors; Transcription, Genetic; proteiny huseníčku; genetická transkripce; Genes, cdc; Spores; CDC geny; Gene Expression Regulation, Developmental; transkripční faktory; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; spory; Haploidy; stanovení celkové genové exprese; Oligonucleotide Array Sequence Analysis; homeodoménové proteiny; Arabidopsis